Parametric equations for involute curves of biharmonic curves in the special three-dimensional ?-Ricci symmetric para-Sasakian manifold P - Körpinar, Talat; Turhan, Essin; Ergüt, Mahmut (International Digital Organization for Scientific Information, 2013)
In this paper, we study involute curve of biharmonic curve in the special three-dimensional ?{symbol}-Ricci symmetric para-Sasakian manifold P. We characterize involute curve of biharmonic curve in terms of curvature and torsion of biharmonic curve in the special three-dimensional ?{symbol}-Ricci symmetric para-Sasakian manifold P. Finally, we find out explicit parametric equations of involute curve of biharmonic curve. © IDOSI Publications, 2013.
Keywords: Biharmonic curve; Involute curve; Para-Sasakian manifold